2020
DOI: 10.3390/nu12041022
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory and Policy-Related Aspects of Calcium Fortification of Foods. Implications for Implementing National Strategies of Calcium Fortification

Abstract: Daily calcium intake is well below current recommendations in most low- and middle-income countries (LMICs). Calcium intake is usually related to bone health, however an adequate calcium intake has also been shown to reduce hypertensive disorders of pregnancy, lower blood pressure and cholesterol values, and to prevent recurrent colorectal adenomas. Fortification of foods has been identified as a cost-effective strategy to overcome micronutrient gaps in public health. This review summarizes regulatory aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 44 publications
1
40
0
1
Order By: Relevance
“…35,36 However, as mentioned previously, the UK is the only country with a mandated calcium fortification program at the national level for wheat flour. 46 However, a few countries have official regulations and/or food standards that provide guidance for voluntary fortification of foods with calcium, which can be implemented by the different food producers. 46 We conducted a thorough review of the literature and institutional webpages, such as Global Fortification Data Exchange and other sources, to gather data on the regulations for calcium fortification of staple foods in different countries.…”
Section: Description Of National Calcium Fortification Programs And/omentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 However, as mentioned previously, the UK is the only country with a mandated calcium fortification program at the national level for wheat flour. 46 However, a few countries have official regulations and/or food standards that provide guidance for voluntary fortification of foods with calcium, which can be implemented by the different food producers. 46 We conducted a thorough review of the literature and institutional webpages, such as Global Fortification Data Exchange and other sources, to gather data on the regulations for calcium fortification of staple foods in different countries.…”
Section: Description Of National Calcium Fortification Programs And/omentioning
confidence: 99%
“…When reviewing the national food fortification efforts that include calcium, we found that calcium may be added to certain staple foods, such as in wheat flour, maize flour or cornmeal, rice, and milk 35,36 . However, as mentioned previously, the UK is the only country with a mandated calcium fortification program at the national level for wheat flour 46 . However, a few countries have official regulations and/or food standards that provide guidance for voluntary fortification of foods with calcium, which can be implemented by the different food producers 46 .…”
Section: Calcium Fortification Programs Worldwidementioning
confidence: 99%
“…Nowadays, more than 130 countries have mandatory food fortification with micronutrients such as iodine, iron, iodine, folate, and vitamin A, however only one country, the UK, has mandatory flour fortification with calcium [ 56 , 57 ]. Even this, the existance of mandatory fortification of foods with other minerals in several countries provides a technological and legal framework that could facilitate the addition of calcium [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 Several countries have established specific regulations for calcium food fortification. 94 Some specify the amount and type of calcium that can be added depending on the food vehicle and other technical details. These regulations are either done proactively, to help promote general health, or reactively, to protect the health and safety of the population.…”
Section: Monitoring and Evaluation Of Calcium-fortified Foodsmentioning
confidence: 99%
“…Fortifying foods with calcium must follow regulations and should be designed within the country's national strategy for the prevention and control of micronutrient deficiencies 16 . Several countries have established specific regulations for calcium food fortification 94 . Some specify the amount and type of calcium that can be added depending on the food vehicle and other technical details.…”
Section: Monitoring and Evaluation Of Calcium‐fortified Foodsmentioning
confidence: 99%